Angular Leaf Spot: A Bacterial Disease in Strawberries in Florida - Natalia A. Peres; Silvia I. Rondon; James F. Price; Daniel J. Cantliffe (EDIS)
Angular Leaf Spot (ALS) is a bacterial disease caused by Xanthomonas fragariae Kennedy & King, a pathogen highly specific to wild and cultivated strawberry, Fragaria x ananassa Duchesne (Legard et al. 2003). ALS is an important disease on winter strawberry production worldwide. In the U.S., it ranks 6th in economic importance after gray mold (Botrytis cinerea L.), verticillium wilt (Verticillium alboatrum Reinke & Berth), powdery mildew (Sphaerotheca macularis L.), anthracnose (Colletotrichum spp.), and pythium root rot (Pythium spp.) (Sorensen et al. 1997). The rapid spread of ALS is influenced by the increasing rate of interchange of plant material. This is document PP-199, a publication of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: June 2004.